Efisiensi Pemanfaatan Lahan pada Tumpangsari Jagung (Zea mays L.) dan Kedelai (Glycine Max L. Merrill) di Lahan Pasang Surut - Iin Siti Aminah; Rosmiah Rosmiah; M. Haris Yahya (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2014)
Tidal swamp is suboptimal land with low fertility rates. This study aims to determine the cropping pattern through intercropping spacing arrangement with biological fertilizer application on corn and soybean. Field research was conducted in the village of tidal swamp Banyu Urip South Sumatra in June-November 2013 using the Split Plot design with the main plot composition Corn planting distance (J) - Soybean (K) i.e. JK 1:3, 1:2 and 1:1; subplot is the provision of biological fertilizer (0, BioP, Azospirillum and BioP + Azospirillum) with 3 replications. Data monoculture corn and soybean as control. Land use on maize soybean intercropping obtained shelled corn and soybean production highest in treatments JK 1:3 with inorganic fertilizer application, although not statistically significantly different (HSD = 0.05). The efficiency ratio is calculated through the land Land Equivalent Ratio (LER) in the treatment of JK 1:3 high of 1.56 whereas the biological fertilizer application LER was 1.69. Competition between plants with CR (competition ratio) of 7.25 occurred at the highest JK 1:1. This study showed a favorable outcome in the land use pattern of intercropping maize planting soybeans in tidal swamps.